The influence of teachers’ professional and pedagogical competence on the enhancement of students’ civic knowledge - Theodorus Pangalila; Brain Fransisco Supit (Jurnal Civics: Media Kajian Kewarganegaraan, 2026)
Civic Education plays a strategic role in shaping students’ awareness of their rights and responsibilities as citizens. However, its effectiveness in Indonesia remains a challenge, particularly in improving students’ civic knowledge. Teachers’ competence, particularly professional and pedagogical competence, is a crucial factor in supporting the quality of teaching and learning. This study aims to examine the influence of teachers’ professional competence (X1) and pedagogical competence (X2) on students’ civic knowledge (Y), both partially and simultaneously. The research employed a quantitative, survey-based approach. The sample consisted of all Grade 11 students taking the Civic Education course at St. Fransiskus Xaverius Seminary Senior High School in Tomohon, selected using a total sampling technique because the entire population that met the study criteria was included (n = 41). The results of the analysis revealed that teachers’ professional competence has a significant effect on improving students’ civic knowledge (the calculated t-value (3.763) > the critical t-value (2.02); sig. 0.001 < 0.05). Teachers’ pedagogical competence also partially shows a significant influence on students’ civic knowledge (the calculated t-value (7.004) > the critical t-value (2.02); sig. 0.000 < 0.05). Simultaneously, both independent variables significantly affect students’ civic knowledge (the calculated F-value (47.273) > the critical F-value (3.24); sig. 0.000 < 0.05). The coefficient of determination (R2) indicates that teachers’ professional and pedagogical competence jointly account for 71.3% of the enhancement of students’ civic knowledge. In comparison, the remaining 28.7% is influenced by other factors not examined in this study.